No way home : a novel - Boyle, T. Coraghessan (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2026)
David Lynch meets Fight Club in T.C. Boyle's No Way Home, an obsessive psychological study that illuminates the darkness that lurks inside all of us.